PERAN PERS DALAM PENINGKATAN DAYA SAING DAERAH - Wicaksono, Kukrit Suryo (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractNewspaper is not only depend on the factors of production, but also outside factors ofproduction are called off-print. One such factor is the newspaper’s role as a "bridge" between thepublic, government, and business. Therefore, Suara Merdeka (hereinafter written: SM) is active asa coordinator of the Organizing Committee (OC) of Survey of Regional Competitiveness in CentralJava 2010. This survey is proof SM role in improving the competitiveness of districts / cities in CentralJava, in addition to as well as best practices that can be used as a model of the newspaper’s role inregional development.